GAMIFICATION-DRIVEN MOTIVATION ENHANCEMENT IN GERMAN LANGUAGE LEARNING: EVIDENCE FROM A DIGITAL PEDAGOGICAL FRAMEWORK - Nursalam Nursalam (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Gamification principles have been demonstrated to enhance motivation and engagement among language learners in the field of foreign language education. A gamified digital learning environment is used to study German as a foreign language among university students. Using a mixed-methods research design with tools measuring learner motivation and learning analytics enabled the collection of data from 35 students enrolled in an A2-level German course. Additionally, semi-structured interviews have provided valuable qualitative insights. The digital gamified system produced in comparison with the standard value an increase in student scores thereby showing the efficacy of this method in enhancing students' In a single variable analysis using t-tests a single variable analysis revealed that 35 of the students exhibited higher language skills in reading, listening, writing and speaking in an introductory German course The sample showed a median initial of 80.09 and a standard deviation of 7.32. The scores of the sample indicated a significant departure from the expected median, with a value of 15.21 and a p-value of 0.001 indicating a statistically significant outcome. This study demonstrates both quantitative improvements in the competence of German students and a shift in the relationship between lecturers and students within the learning equation. It is evident in observations, interviews, and student feedback. The role of a lecturer has undergone a significant transformation in the contemporary academic environment. Historiographically, the primary function of a lecturer was to deliver a lecture to their students. However, the role in the current period has evolved to include a more active involvement in facilitating learning, as well as providing mentorship and designing learning experiences for their students. Historically, students have taken a passive role in the learning environment. Recent observations, regardless, indicate a shift in their engagement with students, with them now actively contributing to the learning process and even creating learning content.